A Potent Mimetic of the Siglec‐8 Ligand 6'‐Sulfo‐Sialyl Lewisx. (31st August 2020) - Kroezen, Blijke S.; Conti, Gabriele; Girardi, Benedetta; Cramer, Jonathan; Jiang, Xiaohua; Rabbani, Said; Müller, Jennifer; Kokot, Maja; Luisoni, Enrico; Ricklin, Daniel; Schwardt, Oliver; Ernst, Beat
Abstract: Siglecs are members of the immunoglobulin gene family containing sialic acid binding N‐terminal domains. Among them, Siglec‐8 is expressed on various cell types of the immune system such as eosinophils, mast cells and weakly on basophils. Cross‐linking of Siglec‐8 with monoclonal antibodies triggers apoptosis in eosinophils and inhibits degranulation of mast cells, making Siglec‐8 a promising target for the treatment of eosinophil‐ and mast cell‐associated diseases such as asthma. The tetrasaccharide 6'‐sulfo‐sialyl Lewis x has been identified as a specific Siglec‐8 ligand in glycan array screening. Here, we describe an extended study enlightening the pharmacophores of 6'‐sulfo‐sialyl Lewis x and the successful development of a high‐affinity mimetic. Retaining the neuraminic acid core, the introduction of a carbocyclic mimetic of the Gal moiety and a sulfonamide substituent in the 9‐position gave a 20‐fold improved binding affinity. Finally, the residence time, which usually is the Achilles tendon of carbohydrate/lectin interactions, could be improved. Abstract : Breathe easy : Siglec‐8 is a promising target for the treatment of eosinophil‐ and mast cell‐associated diseases such as asthma. Based on pharmacophore analysis of 6'‐sulfo‐sialyl Lewis x, a specific Siglec‐8 ligand identified in glycan array screening, potent glycomimetics were developed. While maintaining the neuraminic acid core, a carbocyclic replacement of the Gal moiety and the introduction of a sulfonamide led to a 20‐fold improvement of affinity.